Child self-care autonomy in health (scale for parents): development, internal structure, and sex/age correlates - Mikhaylova, Oxana; Bochkor, Anastasia; Osipova, Polina; Popov, Denis; Chepeleva, Maria; Rybakova, Evgenia (Frontiers in Psychology, 2023)
Autonomy in self-care practices in the health sphere is a critical characteristic for the survival of humans throughout the life span. Notably, however, the current literature lacks psychometrically sound instruments that measure this phenomenon among children without diagnosed chronic health conditions. The purpose of the present exploratory study was to develop, test, and provide data regarding the reliability and validity of the Child Self-Care Autonomy in Health (CSAH) scale. The piloted version of the CSAH yielded an 11-item instrument designed to reflect the parent's perspective in measuring the extent of autonomy in self-care actions related to health for a child, whether diagnosed with a chronic illness or not. Data were collected through an online survey of a non-random sample of Russian-speaking parents currently residing in Russia (N = 349). The analysis focused on scale structure via principal component analysis and age/sex associations. The proposed CSAH may be of interest to social workers, health professionals, and parents seeking to ascertain schoolers' autonomy in self-care practices in the health sphere and support building a stronger selfcare mindset.